More Than One Million Years of History in Lake Ohrid Cores. Issue 3 (21st January 2014) - Wagner, Bernd; Wilke, Thomas; Krastel, Sebastian; Zanchetta, Giovanni; Sulpizio, Roberto; Reicherter, Klaus; Leng, Melanie; Grazhdani, Andon; Trajanovski, Sasho; Levkov, Zlatko; Reed, Jane; Wonik, Thomas
<x xml:space="preserve">Abstract</x> Continental scientific drilling is an important tool for exploring natural and anthropogenic processes on Earth. In past decades the results obtained from lake drilling projects contributed significantly to a better understanding of short‐term and long‐term climate change and natural hazards.